PENGEMBANGAN BAHAN AJAR IPA TERPADU PADA TEMA KELISTRIKAN PADA MAKHLUK HIDUP DENGAN MENGGUNAKAN METODE FOUR STEP TEACHING MATERIAL DEVELOPMENT (4STMD) - Deti Lotaningrat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
This study aims to develop integrated science teaching materials on the theme "Electricity in Living Creatures" by using the Four Step Teaching Material Development Method (4STMD) which includes the Selection, Structuring, Categorization and Reduction of Dactic stages. This research uses Research and Development (R & D) methods. The subject of this study is all science teaching materials on the theme of electricity in living things studied using the 4STMD method. The data in this study were captured by using various types of instruments that were rationally validated (logical) and empirical (empirical) by experts at each stage of development. Data from expert validation were analyzed using CVR and CVI and percentage analysis. The opinions of students regarding the instructional materials developed and the feasibility of the developed teaching materials were collected using questionnaires. As a development evaluation material in the development of teaching materials, the effectiveness of instructional materials on the thinking ability of knowledge integration in students is also tested. As a comparison, also tested the effectiveness of other teaching materials. The effectiveness test results show that students who use teaching materials developed using the 4STMD method have a higher score (65) compared to students who use other teaching materials (60).